Un incontro con Mattia Crespi docente di Geomatica alla Sapienza di Roma (GEOmedia, 2015)
A meeting with Mattia Crespi Mattia Crespi, full professor of Geomatics at La Sapienza University in Rome, to talk about the evolution of Geomatics, the new line of research in the field of 3D sensors and the content of the Italian Spatial Data Infrastructure.